Customer Service Quality in Large Supermarkets in Ibagué, Colombia: Analysis through the SERVQUAL Multidimensional Scale - Guerrero, Germán Rubio (Cuadernos de Administración, 2014)
Globalization is affecting all economies and their organizations seeking to maximize their profits through customer satisfaction. Within this context, large supermarkets have had significant growth; hence, it is important to know the quality of the service customers are receiving in these stores. Currently, service quality measures in these stores in the global market are scarce. This article presents the results of the measurement of the quality of service customers receive from large supermarkets in Ibagué – Colombia, by using the SERVQUAL multi-item scale, which is a tool applied to service quality, comprising five dimensions in 22 items and evaluating characteristics related to tangible aspects, reliability, responsibility, guaranty, security, and empathy. The population studied are customers who visit these supermarkets with mixed research approach (qualitative and quantitative); the results showed customer satisfaction with personnel kindness, customer attention services, agility in attention, customer care, behavior of security personnel, product promoters, merchandisers, cashiers, packers, and supervisors